ALUR DRAMATIK KESENIAN TRADISIONAL SIDALUPA DI ACEH BARAT - Susandro Susandro (Pascasarjana Institut Seni Indonesia Padang Panjang, 2022)
Sidalupa art, on the one hand, is a form of dance without a particular pattern or technique accompanied by serunee and rapa'i music. On the other hand, sometimes it is also made into a form of theatrical performance, marked by the presence of actors, musicians, costume makers, and directors in the process. Today, Sidalupa's art is also packaged with cinematic techniques. This article aims to describe the dramatic flow of Sidalupa art produced by the Datok Rimba and Buraq Lam Tapa art studios in West Aceh which has been produced cinematically based on the ideas of Gustav Freytag; exposition, complication, climax, resolution, and conclusion. This research approach is qualitative with descriptive-analytical method. The techniques applied are video-analysis, observation, content-analysis, literature study, and interviews. The result was that Sidalupa's artistic creation, produced by the Datok Rimba Art Studio, contained quite complex dramatic elements, as did Freytag's idea. Likewise, the chain of events presented shows a coherent series of causes and effects. Meanwhile, the work of the Buraq Lam Tapa group seems to tend to disguise stories and characters as elements that drive events. In other words, it does not contain the complex dramatic elements as stated by Freytag.Keywords: Dramatic Plot; Sidalupa Art; West Aceh.AbstrakKesenian Sidalupa, di satu sisi, ialah sebentuk tarian tanpa pola atau teknik tertentu yang diiringi musik serunee dan rapa’i. Di lain sisi, terkadang juga digarap menjadi sebentuk pertunjukan teater, ditandai dengan adanya aktor, pemusik, pembuat kostum, dan sutradara dalam proses garapannya. Dewasa ini, kesenian Sidalupa dikemas pula dengan teknik sinematik. Artikel ini bertujuan memaparkan alur dramatik kesenian Sidalupa produksi Sanggar Seni Datok Rimba dan Buraq Lam Tapa di Aceh Barat yang digarap secara sinematik berlandaskan pada gagasan Gustav Freytag; eksposisi, komplikasi, klimaks, resolusi, dan konklusi. Pendekatan penelitian ini ialah kualitatif dengan metode deskriptif-analitis. Teknik yang diterapkan adalah video-analisis, observasi, konten-analisis, studi pustaka, dan wawancara. Hasil yang didapati ialah garapan kesenian Sidalupa produksi Sanggar Seni Datok Rimba memuat unsur dramatik yang cukup kompleks, sebagaimana gagasan Freytag. Begitu pula dengan jalinan peristiwa yang dihadirkan, menunjukkan rangkaian sebab-akibat yang runtut. Sedangkan garapan kelompok Buraq Lam Tapa, terkesan cenderung menyamarkan cerita dan tokoh sebagai unsur penggerak peristiwa. Dengan kata lain, tidak memuat unsur dramatik yang kompleks sebagaimana dikemukakan Freytag.Kata Kunci: Alur Dramatik; Kesenian Sidalupa; Aceh Barat